2016
DOI: 10.9734/jamps/2016/31456
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Phytochemical and in vitro Antimicrobial Effects of Solanum lycopersicum Linn. (Tomato) on Oral Thrush and Human Cariogenic Pathogens

Abstract: Aims: Study on the evaluation of phytochemical and antimicrobial effects of tomato Solanum lycopersicum (L.) on oral thrush and human cariogenic pathogens was designed to determine the antimicrobial effect of tomato extracts, and to identify the common phytochemical constituents of tomato that may be inhibitory to oral pathogens. Place and Duration of Study: Fresh tomato fruit samples were collected from Samaru market, Zaria in the month of November and December 2015, and analyzed at Microbiology Laboratory,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 18 publications
(21 reference statements)
1
5
0
Order By: Relevance
“…The use of synthetic and chemically based drugs in the treatment of various bacterial diseases leads to a long-term complication to the recipients, since most of the chemically synthetic drugs possess serious side effects that might make their disadvantages to outweigh their advantages, because some chemical constituents can be carcinogenic, cytolytic or cytotoxic when administered in large doses. Therefore, the use of ethnomedicinal or natural plants as substitutes of chemically synthetic drugs is imperative in order to prevent negative side effects and toxicity of the orthodox drugs with the natural means of treatment [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of synthetic and chemically based drugs in the treatment of various bacterial diseases leads to a long-term complication to the recipients, since most of the chemically synthetic drugs possess serious side effects that might make their disadvantages to outweigh their advantages, because some chemical constituents can be carcinogenic, cytolytic or cytotoxic when administered in large doses. Therefore, the use of ethnomedicinal or natural plants as substitutes of chemically synthetic drugs is imperative in order to prevent negative side effects and toxicity of the orthodox drugs with the natural means of treatment [1].…”
Section: Introductionmentioning
confidence: 99%
“…Also, gastrointestinal disorders, dysentery, diarrhoea and candidiasis are very serious infections that can lead to frequent morbidity and mortality in tropical countries like Nigeria. These disorders are serious diseases that can affect many people at various stages of their lives causing distress and discomfort [1]. Sometimes, the disorder can even lead to hospitalization.…”
Section: Introductionmentioning
confidence: 99%
“…We found a high percentage of growth inhibition (≄100%) against these bacteria at a concentration of 500 mg/L. Only one study, conducted in Nigeria, has previously evaluated the antimicrobial effect of tomatoes against S. mutans (19). The authors reported that aqueous and methanolic extracts had no inhibitory effect on this microorganism at various concentrations (12.5, 25, 50, and 100 mg/mL).…”
Section: Discussionmentioning
confidence: 77%
“…Of note, all the five different extracts tested (i.e., chloroform, methanol, ethyl acetate, hexane, and sulfuric acid) were active against C. albicans, except for the ethyl acetate extract. Other studies have found no growth-inhibiting activity of tomato fruit aqueous and methanolic extracts against C. albicans (19,22). Hence, the contrasting results might be attributed to the solvents used in the extraction protocols, as it has been shown that the solubility of antimicrobial and antioxidant compounds in tomato extracts largely depends on the solvent polarity (23).…”
Section: Discussionmentioning
confidence: 92%
“…(11 ± 0.12) [251]. At 0.5 mg/ml acetone and methanol extracts exhibited activity against against S. pyogenes [252].…”
Section: Yam (Dioscorea Spp)mentioning
confidence: 99%